Young Buddhists and the Cosmopolitan Irony of Belonging in Multicultural Australia. (2nd November 2019) - Lam, Kim
ABSTRACT: While existing research shows low levels of negative sentiment towards Buddhists in Australia, little is known about their lived experiences of belonging, and what they do to facilitate social cohesion. This article addresses this gap by exploring experiences of belonging and intercultural engagement among twenty-two young adult Buddhists from a range of backgrounds living in Australia. It finds that while multiculturalism and positive portrayals of Buddhism facilitated the belonging of these young Buddhists, anti-religious sentiment and processes of racialisation contributed to experiences of exclusion. The article contends that these contradictory forces create an ambiguous context for the negotiation of religious belonging and intercultural engagement, which study participants addressed through processes of contextualisation, accommodation and reflexive community-building. It further suggests that Bryan Turner's concept of cosmopolitan irony provides a useful lens through which to unpack these complexities.